Influence of 2D and 3D body segment models on energy calculations during kinematic analysis of running - Metzler, V.; Arampatzis, A.; Brüggemann, G. P. (European Journal of Applied Physiology, 2002)
The aims of the present study were: (1) to examine the influence of two-dimensional (2D) and three-dimensional (3D) analysis on the body's total energy during the support phase of running, and (2) to examine the influence of the choice of anthropometric models on the body's total energy during running. A total of 14 runners participated in the investigation [mean (SD) height: 1.83 (0.03) m, body mass: 79.67 (5.65) kg]. Two genlocked high-speed cameras (120 Hz) filmed each athlete's movement during single-foot ground contact. The exact support time of the athletes was measured with a Kistler force plate (sampling frequency: 1000 Hz). The masses and moments of inertia of the various segments were estimated using the 2D and 3D models of Hanavan (1964) as well as the 3D model of Zatsiorsky et al. (1984).The influence of the 2D and 3D analysis on the calculations was evaluated by comparing of the total energies calculated using Hanavan's 2D and 3D models. The influence of the choice of the anthropometric model on the calculations was checked by comparing the results obtained using the Hanavan 3D model and those obtained using the 3D model of Zatsiorsky et al. (1984). The data show us that 2D and 3D analyses produce similar energy values during the entire support phase of running (only very small percentage energy differences were observed: e.g. from 0.23% for the energy of the body at the first contact with the ground, up to 0.31% for the energy of the body at the time the athlete leaves the ground, ETO). In addition, calculations made using the 3D models of Hanavan and Zatsiorsky also produced similar results for energy values (energy differences from 0.33% for energy minimum, up to 0.8% for ETO). It can be assumed, therefore, that neither the choice of the anthropometric model nor the calculations made on the basis of 3D coordinates are limiting factors in the calculation of body total energies for running.